Healthcare resource utilization in patients receiving idarucizumab for reversal of dabigatran anticoagulation due to major bleeding, urgent surgery, or procedural interventions: interim results from the RE-VERSE AD™ study. (4th May 2017) - Pollack, Charles V.; Bernstein, Richard; Dubiel, Robert; Reilly, Paul; Gruenenfelder, Fredrik; Huisman, Menno V.; Kam, Chak-Wah; Kleine, Eva; Levy, Jerrold H.; Sellke, Frank W.; Steiner, Thorsten; Ustyugova, Anastasia; et al.
Abstract: Aims: Patients treated with anticoagulants may experience serious bleeding or require urgent surgery or intervention, and may benefit from rapid anticoagulant reversal. This exploratory analysis assessed healthcare resource utilization (HCRU) in patients treated with idarucizumab, a specific reversal agent for dabigatran etexilate. Materials and methods: RE-VERSE AD™ (NCT02104947), a prospective, multi-center open-label study, is evaluating idarucizumab for dabigatran reversal in patients with serious bleeding (Group A) or undergoing emergency surgery/procedures (Group B). HCRU outcome measures evaluated in the first 90 patients enrolled were use of blood products and pro-hemostatic agents, length of stay (LOS) in hospital, and LOS in intensive care unit (ICU). Results: Blood products or pro-hemostatic agents were given to 63% (32/51) of patients in Group A and 23% (9/39) of patients in Group B on the day of/day after surgery. An overnight hospital stay was reported for 82% (42/51) of patients in Group A with median LOS = 7 (range = 1–71) bed-days. For Group B, 92% (36/39) had an overnight hospital stay with a median LOS = 9 (range = 1–92) bed-days. In Group A, 17 patients were admitted to the ICU for at least 1 day with median LOS = 4 (range = 1–44) days; in Group B the number was 15 with median LOS = 2 (range = 1–92) days. Limitations: The lack of a control group and the small patient numbers limit the strength of the conclusions. Conclusions: The use of idarucizumab may simplify emergency management of dabigatran-treated patients with life-threatening bleeds and reduce perioperative complications in patients undergoing emergency surgery.